Activating ALK mutations found in neuroblastoma are inhibited by Crizotinib and NVP-TAE684. - Schönherr, C.; Ruuth, K.; Yamazaki, Y.; Eriksson, T.; Christensen, J.; Palmer, R.H.; Hallberg, B. (The Biochemical Journal, 2011)
Mutations in the kinase domain of ALK (anaplastic lymphoma kinase) have recently been shown to be important for the progression of the childhood tumour neuroblastoma. In the present study we investigate six of the putative reported constitutively active ALK mutations, in positions G1128A, I1171N, F1174L, R1192P, F1245C and R1275Q. Our analyses were performed in cell-culture-based systems with both mouse and human ALK mutant variants and subsequently in a Drosophila melanogaster model system. Our investigation addressed the transforming potential of the putative gain-of-function ALK mutations as well as their signalling potential and the ability of two ATP-competitive inhibitors, Crizotinib (PF-02341066) and NVP-TAE684, to abrogate the activity of ALK. The results of the present study indicate that all mutations tested are of an activating nature and thus are implicated in tumour initiation or progression of neuroblastoma. Importantly for neuroblastoma patients, all ALK mutations used in the present study can be blocked by the inhibitors, although some mutants exhibited higher levels of drug sensitivity than others.